Elektabilitas Tanpa Legitimasi Agama: Peran Marginal Tokoh Agama dalam Dinamika Elektoral PSI di DKI Jakarta - Muhamad Ihya Ahsana; Rahmat Hidayatullah (Inklusiva: Jurnal Studi Agama-Agama, 2025)
This research analyzes the role of religious figures in the electoral dynamics of the Indonesian Solidarity Party (PSI) in DKI Jakarta, a region known for its strong political identity polarization. PSI presents an anomaly because it positions itself as a modern party that rejects the politicization of religion, yet it has managed to maintain significant electability. The results of the qualitative analysis show that the role of support and legitimacy from religious figures is marginal and not essential in the formation of PSI's electoral base, thereby rejecting the hypothesis of the centrality of religious legitimacy. PSI's electability is driven by non-primordial factors, including its appeal to urban young voters (Millennials and Gen Z), its commitment to performance and anti-corruption issues, and the construction of a political identity as a modern/secular opposition to religion-based parties. The existing role of religious figures is limited to the personal, educational, and dialogical realms, rather than institutional mass mobilization. These findings introduce the concept of "Electability Without Religious Legitimacy" and verify the shift in political cleavage from a primordial basis to a generational and modernist-vs-traditionalist ideological basis in Indonesian urban politics.